Analisis Potensi dan Strategi Pengembangan Bisnis Peternakan Babi di Wilayah Kota Samarinda - Cori Qamara; I Putu Gede Didik Widiarta (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Pig farming is crucial in local economies and food security, providing a vital protein source and economic opportunities. In Samarinda City, East Kalimantan, the sector demonstrates significant potential due to abundant natural resources and rising market demand, contributing 15% of the province’s pork production in 2024. This study examines strategies for developing pig farming businesses in Samarinda City using a mixed-methods approach, integrating descriptive and analytical methods. Data were collected through surveys and interviews with 50 respondents, including farmers, traders, and policymakers, complemented by secondary data from government agencies. Analytical tools such as SWOT, Location Quotient (LQ), and multiple regression were employed. The findings reveal that Samarinda Utara and Palaran have the highest specialization in pig farming, with LQ values of 1.8 and 1.7, supported by ample land and feed resources. Key drivers of farmer income include production scale and policy support, while high feed costs, comprising up to 70% of production expenses, remain a significant challenge. Recommendations include diversifying pork-based products, adopting modern technologies, strengthening policies, and improving distribution infrastructure. This research provides actionable insights to enhance the sustainability and competitiveness of pig farming, contributing to regional economic development and agricultural resilience.